APLIKASI TEMBANG MACAPAT BERBASIS MULTIMEDIA - Agustin Setyorini (Informasi Interaktif, 2016)
In the grammar of Java is much to be learned include Javanese, Tembung, Ater-atr Seselan Panambangan, Homonin, antonyms, synonyms, Ukara, Proverb Java, Purwakanthi, Song, Gendhing and Karawitan, Fiber, Babad, puppets and much more. At this time only a few children who are familiar with the Java language's grammar. This is usually because the very basis of the delivery of material that is less attractive so that children feel bored quickly. Advances in technology today, perceived benefits in various fields, such as creating a media that can facilitate the child in learning something. In general, media that can be used to learn the language of children, visual media and audio media. Kids learn about the environment and absorbing knowledge through what is seen and heard, so that the sense of sight and hearing is the gateway entrance of science into the child. To more easily learn the Java language, can be made a apliksai to learn the Java language-based multimedia. One of the Java grammar that will be created apliksinya is Macapat song. The purpose of this study was to design and to design an instructional media to learn the song Macapat. This research is expected to facilitate the children in the study of grammar Java one of which is the song Macapat.Keyword : Javanese grammar, song Macapat, Learning Media, Multimedia.